2010
DOI: 10.3923/pjbs.2010.743.747
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Selenite-induced Cataractogenesis by Origanum vulgare Extract

Abstract: The present study sought to assess antioxidant effect of Origanum vulgare extract in preventing selenite-induced cataractogenesis. This study was performed on Young white rats received sodium selenite (30 nmol g(-1) birth weight) subcutaneously on day 13 post partum during two months in 2009. Cataract formation and intensity was detected and measured by slit-lamp. Origanum vulgare (Ov) extract (2 g kg(-1)) was given (1-2 times) intraperitoneal at different times with respect to the selenite administration lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Ocimum sanctum (Lamiaceae) Extract of plant inhibition of polyol accumulation (Halder et al, 2003) Origanum vulgare Extract of plant Inhibit the oxidative damage and reduces the lipid peroxidation. (Dailami et al, 2010) Pterocarpus marsupium (Fabaceae) aqueous extract Inhibits the diabetes induced cataract (Vats et al, 2004) Silybum marianum (Compositae) seeds extract Inhibit the oxidative damage (Huseini et al,2004) Trigonella foenum graceum (Fabaceae) Seed extract Inhibit the generated oxidative stress (Lija et al, 2006) Vitex negundo (verbanaceae) flavonoids fraction Inhibits the oxidative stress (Rooban et al, 2011) Withania somnifera (solanaceae) Extract of plant Inhibits the oxidative stress (Thiagarajan et al, 2003) PLANT PRODUCTS AGAINST CATARACTS reactive oxygen species, which causes the lipid peroxidations and thus play major role in development of diabetic secondary complications in kidney, blood vessels, eye and nerve . The natural antioxidant such as ascorbic acid, vitamin E, and carotinoids have been screened and it was found that antioxidant has protective action against cataract.…”
Section: Plant Products Against Cataractsmentioning
confidence: 99%
“…Ocimum sanctum (Lamiaceae) Extract of plant inhibition of polyol accumulation (Halder et al, 2003) Origanum vulgare Extract of plant Inhibit the oxidative damage and reduces the lipid peroxidation. (Dailami et al, 2010) Pterocarpus marsupium (Fabaceae) aqueous extract Inhibits the diabetes induced cataract (Vats et al, 2004) Silybum marianum (Compositae) seeds extract Inhibit the oxidative damage (Huseini et al,2004) Trigonella foenum graceum (Fabaceae) Seed extract Inhibit the generated oxidative stress (Lija et al, 2006) Vitex negundo (verbanaceae) flavonoids fraction Inhibits the oxidative stress (Rooban et al, 2011) Withania somnifera (solanaceae) Extract of plant Inhibits the oxidative stress (Thiagarajan et al, 2003) PLANT PRODUCTS AGAINST CATARACTS reactive oxygen species, which causes the lipid peroxidations and thus play major role in development of diabetic secondary complications in kidney, blood vessels, eye and nerve . The natural antioxidant such as ascorbic acid, vitamin E, and carotinoids have been screened and it was found that antioxidant has protective action against cataract.…”
Section: Plant Products Against Cataractsmentioning
confidence: 99%
“…Oregano retards aging and degenerative diseases through antioxidant defense mechanisms. 36 These antioxidant mechanisms include preventing oxidation-induced DNA damage and enhancing the antioxidant response elements and enzymes. 37 Other herbs with very high ORAC values are Catharanthus roseus, Thymus vulgaris, Hypericum perforatum and Artemisia annua.…”
Section: Oregano (Origanum Vulgare)mentioning
confidence: 99%